Tracing the pathway from mental health screening to services for children and youth in foster care. (June 2018) - Pullmann, Michael D.; Jacobson, Jedediah; Parker, Elizabeth; Cevasco, Molly; Uomoto, Jacqueline A.; Putnam, Barbara J.; Benshoof, Trishia; Kerns, Suzanne E.U.
Abstract: Purpose: Children and youth in out-of-home care have high rates of behavioral health need, and states are increasingly adopting screening protocols to identify and intervene with these youth. This study presents longitudinal analyses of the case flow of youth aged 3–17 in Washington State's foster care system, tracking rates of screening, scoring above or below clinical criteria cutoff scores, and service receipt. This study describes what variables are associated with these three decision points. Results: Eighty-nine percent of eligible youth were screened for behavioral health need soon after entry in to out-of-home care; most of those who were not screened were already receiving behavioral health services. Sixty-one percent scored above criteria on at least one screening measure by at least one respondent. Sixty percent of those who scored above criteria and 33% of those who scored below criteria received at least one behavioral health service within 4 months of entry to care. After controlling for all variables, screening above criteria was related to age, race/ethnicity, county rurality, abuse type, reason for out-of-home placement, past behavioral health service receipt, and type of past diagnosis. Service receipt for those scoring above criteria was related to age, race/ethnicity, county rurality, abuse type, and type of prior behavioral health diagnosis. Conclusions: The role of screening in child welfare is dynamic and influenced by multiple factors. In the current study, youth screening above criteria was related to increased rates of service receipt. However, many children with behavioral health service needs did not receive services. The relatively high rates of youth scoring below criteria but receiving services may indicate a need for ongoing systematic screening in order to identify emergent needs, or additional screening measures at intake. States considering or employing the use of screening tools should weigh a variety of approaches to screening, assessment, and referral to services in order to ensure maximal benefit. Graphical abstract: Pathway of screening and service receipt for children and youth entering foster care. Note: Study population is all children aged 3–17.5 entering out of home care for 30 days or more between July 2010 and July 2014. "Screened above criteria" indicates that the youth scored above established clinically significant criteria at least on mental health measure by at least one reporter (e.g. self-report, parent, teacher), indicating further assessment may be warranted. Mental health service receipt includes at least one mental health service on at least one occasion during the time period (e.g. assessment, outpatient therapy, hospitalization). Highlights: 89% of youth entering foster care were screened for mental health symptoms. 61% screen above clinical cutoff, indicating a mental health need Age, race, gender, and maltreatment type were associated with screening outcomes. Those scoring above cutoff were twice as likely to receive mental health services. Older age, physical/sexual abuse, and psychiatric diagnoses predicted service receipt.